Estudio de prefactibilidad para la instalación de una planta de producción de limpiadores líquidos desengrasantes a base de cáscara de naranja (Exocarpio de citrus sinensis), yuca (Manihot esculenta) y bicarbonato de sodio - Arias Ribeiro, Karen Melissa (2022)
Currently, there is no company in the national market that dedicates its activities to the production and distribution of eco-friendly cleaning products. However, there is a high demand. Focusing on this and with expansion ambitions, the business idea of this project is proposed. The purpose of which is to determine the technical, economic, financial and social viability through a pre-feasibility study for the installation of a production plant for liquid degreasing cleaners based on natural products. This research seeks to take advantage of the properties of natural products such as cassava, orange peel and sodium bicarbonate for cleaning grease residues from different surfaces, highlighting the non-contribution to environmental pollution or damage to the environment. consumer health. It is determined that there is a fairly large potential market for the product, likewise, the demand for the project in the first and last year reaches a value of 49,061 and 66,775 bottles of 500 ml respectively. The production plant will be located in the department and province of Lima, district of Lurín and will have a production capacity of 67,681 500 ml bottles. Regarding the selection of technology, all the required machinery is available and for sale in the market. Likewise, technical standards, methods and control measures have been considered to guarantee the quality of the entire process. Finally, and after carrying out the study of expenses and respective costs, it was determined that the implementation of a production plant for liquid cleaners based on orange peel, cassava and sodium bicarbonate is economically, environmentally and socially viable in the conditions of market to be developed.